2022
DOI: 10.1016/j.mayocp.2021.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Monoclonal Antibodies in Preventing Severe COVID-19 With Emergence of the Delta Variant

Abstract: Anti-spike monoclonal antibodies have proven invaluable in preventing severe outcomes from COVID-19, including hospitalization and death. The rise of the SARS-CoV-2 Delta variant begs the question of whether monoclonal antibodies maintain similar efficacy now as they had when the alpha and beta variants predominated, when they were first assessed and approved. We used a retrospective cohort to compare rates of severe outcomes in an epoch where alpha and beta were predominant compared to delta. A total of 5,356… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…These findings are consistent with those of a previous study conducted in the United States reporting the possibility of reduced monoclonal antibody effectiveness in a real-world setting during the Delta-predominant period [ 16 ]. As recent studies suggested reduced monoclonal antibody efficacy and neutralization by vaccinated serum of the new variant of concern, omicron [ 17 18 ], we could expect that the clinical effectiveness of regdanvimab may decrease when other new variant becomes dominant, similar to the Delta variant.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with those of a previous study conducted in the United States reporting the possibility of reduced monoclonal antibody effectiveness in a real-world setting during the Delta-predominant period [ 16 ]. As recent studies suggested reduced monoclonal antibody efficacy and neutralization by vaccinated serum of the new variant of concern, omicron [ 17 18 ], we could expect that the clinical effectiveness of regdanvimab may decrease when other new variant becomes dominant, similar to the Delta variant.…”
Section: Discussionsupporting
confidence: 92%
“…Patient medical conditions, vaccination history, medications used at time of diagnosis, height and weight, self-reported race and ethnicity, and home zip code were obtained from the EHR. Recorded medical conditions and age were used to calculate the monoclonal antibody screening score (MASS), a comorbidity index that is predictive of COVID-19 hospitalization risk, 6,7 for each patient. Patients were considered immunocompromised if they were receiving immunosuppressive medications (eg, prednisone, TNF inhibitors, calcineurin inhibitors, mTOR inhibitors, anti-CD20 antibodies), had an active malignancy, received a stem cell or solid organ transplant, or HIV infection irrespective of CD4 cell count.…”
Section: Patientsmentioning
confidence: 99%
“…With fluctuating rates of transmission of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), readily available neutralizing monoclonal antibody (mAb) products such as sotrovimab for outpatients who have recently tested positive for SARS-CoV-2 has been a critical, evidence-based treatment strategy to mitigate the impact of COVID-19 surges on the health care system and improve COVID-19 outcomes among high-risk individuals. [1][2][3][4][5][6][7] Several mAb products received emergency use authorization (EUA) from the US Food and Drug Administration [8] based on Phase II/III randomized clinical trials conducted earlier in the pandemic that demonstrated efficacy towards reduced hospitalization and disease severity among high-risk outpatients, [9][10][11] but little randomized data is available to inform mAb efficacy against new variants including Omicron lineages that have rapidly evolved. [12] As such, analysis of more contemporaneous real-world data sufficiently robust to evaluate important clinical differences is critical to evaluate treatment effectiveness and inform policy and practice decisions, as we and others have successfully done.…”
Section: Introductionmentioning
confidence: 99%
“…[12] As such, analysis of more contemporaneous real-world data sufficiently robust to evaluate important clinical differences is critical to evaluate treatment effectiveness and inform policy and practice decisions, as we and others have successfully done. [3][4][5][6][7] We previously used a real-world data platform to report on sotrovimab effectiveness during the Delta variant pandemic phase, [2] adding to the evidence generated from the COMET-ICE trial that found a significant reduction in risk of a composite endpoint of all-cause hospitalization or death following sotrovimab treatment [10] and led to emergency use authorization (EUA) for sotrovimab (May 26, 2021). Subsequently, when EUAs for other authorized mAbs were revoked in January 2022, sotrovimab was the only available mAb for outpatient treatment during early Omicron.…”
Section: Introductionmentioning
confidence: 99%